Comorbid conditions and health-related quality of life among hypertensive patients. - Khaw, Wan Fei; Abd Latiff, Latiffah; Syed Hassan, Syed Tajuddin (Drunpp-Sarajevo, 2011)
Hypertension and its comorbid conditions mayaffect patients’ quality of life. This study is to de-termine the relationship between comorbid condi-tions and health-related quality of life (HRQOL) inhypertensive patients. A total of 173 hypertensivepatients were included in this cross-sectional study.Data on sociodemography, prevalence of comor-bid conditions, and the Medical Outcomes Study36-item Short-Form Health Survey (SF-36) scoreson HRQOL were obtained through guided intervi-ew, using pre-tested questionnaires. The influenceof sociodemography and comorbid conditions onSF-36 scores was assessed. Age, gender, and edu-cational level affected most domains of SF-36 scalenegatively. Hypertensive patients with heart diseasecondition recorded lower scores in most of the SF-36 domains. Diabetes too affected negatively fivedomains especially the physical constructs. Previ-ous stroke has a negative impact on physical fun-ctioning, general health, vitality, and mental health,whereas the negative influence of nephropathy onlyaffected physical functioning. We conclude thathypertension and comorbid conditions are associ-ated with decreases in HRQOL. Therefore, preven-ting or reducing the complications of hypertensionis needed in order to improve quality of life amonghypertensive patients.